2020
DOI: 10.1021/acs.energyfuels.9b04258
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Solvent Extraction and Noncatalytic Esterification for the Treatment of Acidic Feedstocks

Abstract: The possibility of directly feeding the extract of a liquid−liquid extraction unit to a chemical reactor is analyzed. An example of extraction and noncatalytic esterification of naphthenic acids from acid petroleum crudes is used. Methanol is used both as a solvent and as a reactant. Separate tests of extraction and reaction are performed, and the performance of an integrated process is deduced by computer simulation. Thermodynamic and kinetic parameters for the extraction of naphthenic acids from an acid crud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…For conducting transesterification at very high temperature and pressure, the previous researchers reported the reactor and accessories made of stainless steel grade of 304 and 316, which is itself a costly material in the engineering field. The authors also reported no reactivity of reactant media with SS‐316 and SS‐304 36,37 . Although, a search for better and feasible material can also be the future scope from the reactor design point of view.…”
Section: Supercritical Transesterification and Its Limitationsmentioning
confidence: 97%
See 1 more Smart Citation
“…For conducting transesterification at very high temperature and pressure, the previous researchers reported the reactor and accessories made of stainless steel grade of 304 and 316, which is itself a costly material in the engineering field. The authors also reported no reactivity of reactant media with SS‐316 and SS‐304 36,37 . Although, a search for better and feasible material can also be the future scope from the reactor design point of view.…”
Section: Supercritical Transesterification and Its Limitationsmentioning
confidence: 97%
“…Lamba et al 85 concluded the superiority of this method for Neem and Mahua as feedstock and reported the yield of 83% in 15 min and 99% in 10 min, respectively. Naphthenic acid was also tried as feedstock for supercritical esterification and found the end product a good fuel additive 36 . Some of the past investigations are showing exciting results for algae and stabilizing it as the future's most productive feedstock for biodiesel production 35,45,90 …”
Section: Supercritical Transesterification and Its Limitationsmentioning
confidence: 99%